Method for producing precursor of positive electrode active material and method for producing positive electrode active material

CN122916239APending Publication Date: 2026-10-16PRIME PLANET ENERGY & SOLUTIONS INC +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610399880.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-09
Filing Date
2026-03-30
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,在这种情况下,存在如下问题:Mn首先优先析出,在最终得到的碳酸盐的粒子中,Mn不均匀分布于粒子的中心部

Benefits of technology

[0012] Based on this structure, a precursor for a positive electrode active material can be manufactured that suppresses the uneven distribution of Mn at the center of the particle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916239A_ABST
    Figure CN122916239A_ABST
Patent Text Reader

Abstract

Provided is a method for producing a precursor of a positive electrode active material in which the uneven distribution of Mn in the center of particles is suppressed. The method for producing a precursor of a positive electrode active material according to the present disclosure includes a crystallization step of adding a raw material solution containing Ni, Co, Mn, ammonia, ammonium ions, and carbonate ions to a precipitation liquid to precipitate a carbonate containing Ni, Co, and Mn. The concentration of ammonia in the precipitation liquid is lower than the concentration of ammonia in the raw material solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to a method for manufacturing a precursor of a positive electrode active material. This disclosure also relates to a method for manufacturing the positive electrode active material. It should be noted that this application claims priority to Japanese Patent Application No. 2025-064483, filed April 9, 2025, the entire contents of which are incorporated herein by reference. Background Technology

[0002] Lithium-ion secondary batteries are widely used in various fields, such as vehicle power supplies and portable power sources. In the manufacture of the positive electrode active material used in the positive electrode of lithium-ion secondary batteries, typically, a hydroxide or carbonate containing a metal source other than Li is first produced as a precursor via crystallization. For example, when manufacturing carbonates as precursors for lithium transition metal complex oxides, a crystallization reaction is performed using a reaction solution containing a transition metal, ammonium ions, and carbonate ions (see, for example, Patent Document 1).

[0003] On the other hand, from the perspective of the SDGs, the recycling of materials from used lithium-ion secondary batteries is being promoted in recent years. Regarding material recycling, technologies are being developed to separate metal elements contained in the positive electrode active material from used lithium-ion secondary batteries and reuse them in the manufacture of positive electrode active materials. As an example, an ammonia leachate containing Ni and Co can be obtained from battery waste through ammonia leaching (see, for example, Non-Patent Literature 1).

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: International Publication No. 2017 / 119457

[0007] Non-patent literature

[0008] Non-patent literature 1: Waste Management, February 2017, vol.60, pp.680-688 Summary of the Invention

[0009] The inventors conducted in-depth research and discovered the following: In the recycling of materials from lithium-ion secondary batteries, a leachate containing Ni, Co, Mn, ammonia, ammonium ions, and carbonate ions can be obtained by ammonia leaching. Furthermore, by evaporating ammonia from this leachate, a nickel-cobalt-manganese composite carbonate, a precursor for the positive electrode active material, can be generated. However, in this case, the following problem exists: Mn preferentially precipitates first, resulting in an uneven distribution of Mn in the central portion of the final carbonate particles. When Mn is unevenly distributed in the central portion of the particles, the amount of Ni in the surface layer increases, which may lead to instability in the crystal structure of the positive electrode active material.

[0010] Therefore, the purpose of this disclosure is to provide a method for manufacturing a precursor of a positively active material that suppresses the uneven distribution of Mn at the center of the particle.

[0011] The method for manufacturing the precursor of the positive electrode active material disclosed herein includes the following steps: adding a feed solution containing Ni, Co, Mn, ammonia, ammonium ions, and carbonate ions to a precipitation solution, thereby precipitating carbonates containing Ni, Co, and Mn. The concentration of ammonia in the precipitation solution is lower than the concentration of ammonia in the feed solution.

[0012] Based on this structure, a precursor for a positive electrode active material can be manufactured that suppresses the uneven distribution of Mn at the center of the particle. Attached Figure Description

[0013] Figure 1 This is a flowchart illustrating the various steps involved in the recycling of waste from lithium-ion secondary batteries, including the steps of the method for manufacturing the precursor of the positive electrode active material disclosed herein.

[0014] Figure 2 This is a longitudinal cross-sectional view schematically representing the internal structure of an example of a lithium-ion secondary battery.

[0015] Figure 3 It means Figure 2 The diagram shows an exploded view of the electrode structure of a lithium-ion secondary battery.

[0016] Figure 4 This is a cross-sectional SEM image of the nickel-cobalt-manganese composite carbonate particles obtained in Comparative Example 1.

[0017] Figure 5 This is a cross-sectional Mn mapping image of the nickel-cobalt-manganese composite carbonate particles obtained in Comparative Example 1.

[0018] Figure 6 This is a Ni-mapped image of the cross-section of the nickel-cobalt-manganese composite carbonate particles obtained in Comparative Example 1.

[0019] Figure 7This is a cross-sectional SEM image of the nickel-cobalt-manganese composite carbonate particles obtained in Example 4.

[0020] Figure 8 This is a cross-sectional Mn mapping image of the nickel-cobalt-manganese composite carbonate particles obtained in Example 4.

[0021] Figure 9 This is a Ni-mapping image of the cross-section of the nickel-cobalt-manganese composite carbonate particles obtained in Example 4. Detailed Implementation

[0022] The embodiments of this disclosure will now be described with reference to the accompanying drawings. It should be noted that matters not mentioned in this specification but necessary for the implementation of this disclosure can be grasped by those skilled in the art based on existing technology in the field. This disclosure can be implemented based on the content disclosed in this specification and common technical knowledge in the field. Furthermore, in the following drawings, components and parts that perform the same function are labeled with the same symbols. Additionally, the dimensional relationships (length, width, thickness, etc.) in the drawings do not reflect actual dimensional relationships. It should be noted that the numerical range represented as "A~B" in this specification includes both A and B.

[0023] It should be noted that in this specification, "secondary battery" refers to an energy storage device capable of repeated charging and discharging. Furthermore, in this specification, "lithium-ion secondary battery" refers to a secondary battery that utilizes lithium ions as charge carriers and achieves charging and discharging through the movement of lithium ions between the positive and negative electrodes.

[0024] The method for manufacturing the precursor of the positive electrode active material disclosed herein includes the following steps: reacting nickel (Ni), cobalt (Co), manganese (Mn), ammonia (NH3), and ammonium ions (NH4)... + ) and carbonate ions (CO3) 2- The feed solution is added to the precipitation solution to precipitate carbonates containing Ni, Co, and Mn (hereinafter also referred to as the "crystallization process"). Here, the concentration of ammonia in the precipitation solution is lower than the concentration of ammonia in the feed solution.

[0025] The raw material liquid used in the manufacturing method disclosed herein can be generated during the recycling of waste from lithium-ion secondary batteries. Therefore, Figure 1 This describes a series of recycling processes for waste materials from lithium-ion secondary batteries, utilizing the method for manufacturing precursors of the positive electrode active material disclosed herein. It should be noted that... Figure 1 The necessary step in the method for manufacturing the precursor of the positive electrode active material of this disclosure is the crystallization step S110, and the other steps are arbitrary steps.

[0026] Therefore, the method for manufacturing the precursor of the positive electrode active material disclosed herein may involve material recycling for secondary batteries (especially lithium-ion secondary batteries). Therefore, a general configuration example of a lithium-ion secondary battery will be described first.

[0027] <Lithium-ion secondary batteries>

[0028] An example of the structure of a lithium-ion secondary battery is shown below. Figure 2 and Figure 3 . Figure 2 This is a longitudinal cross-sectional view schematically representing the internal structure of an example of a lithium-ion secondary battery. Figure 3 It is a schematic representation Figure 2 The diagram shows an exploded view of the electrode body of a lithium-ion secondary battery. It should be noted that the following description of the lithium-ion secondary battery is for ease of understanding and does not in any way limit the method for manufacturing the precursor of the positive electrode active material disclosed herein.

[0029] like Figure 2 As shown, the lithium-ion secondary battery 100 is a sealed battery in which a flat electrode 20 and a non-aqueous electrolyte (not shown) are housed inside the battery casing 30. Figure 2 As shown, the battery casing 30 consists of an outer body 32 that houses the electrode body 20 and a cover 34 that seals the opening of the outer body 32. The outer body 32 and the cover 34 are sealed by welding, such as laser welding. Materials used for the battery casing 30 include, for example, aluminum, aluminum alloy, and resin.

[0030] In the example shown, the battery casing 30 is square. However, the shape of the battery casing 30 is not limited to this; for example, it can be cylindrical. Alternatively, the battery casing 30 can be a laminated casing having a gas barrier layer, such as an aluminum layer, and a sealing layer containing a thermoplastic resin.

[0031] The battery casing 30 has a positive terminal 42 and a negative terminal 44 for external connection. Additionally, a safety valve 36 is provided in the battery casing 30, which is configured to release internal pressure when the internal pressure of the battery casing 30 rises above a predetermined level. An injection port (not shown) for injecting a non-aqueous electrolyte is provided in the battery casing 30. The positive terminal 42 is electrically connected to the positive current collector 42a. The negative terminal 44 is electrically connected to the negative current collector 44a.

[0032] like Figure 2 and Figure 3 As shown, the electrode body 20 has a strip-shaped positive electrode 50 and a strip-shaped negative electrode 60, which are formed by overlapping two strip-shaped insulating sheets 70 and wound along their long sides. Therefore, in this embodiment, the electrode body 20 is a wound electrode body. However, the electrode body 20 is not limited to this, and may also be a stacked electrode body in which multiple positive electrodes and multiple negative electrodes are alternately stacked by insulating sheets.

[0033] like Figure 2 As shown, in the positive electrode 50, a positive active material layer 54 is formed on one or both sides (in this case, both sides) of the positive current collector 52 along the long side direction. The positive electrode 50 has a portion where the positive active material layer 54 is not formed and the positive current collector 52 is exposed, namely, the non-formed portion 52a of the positive active material layer. A positive current collector plate 42a is bonded to the non-formed portion 52a of the positive active material layer.

[0034] Examples of positive current collectors 52 constituting the positive electrode sheet 50 include aluminum foil. The positive electrode active material layer 54 contains a positive electrode active material. A typical positive electrode active material is a lithium nickel cobalt manganese composite oxide. The positive electrode active material layer 54 may contain conductive materials (such as carbon black, carbon nanotubes, etc.), binders (such as polyvinylidene fluoride, etc.), etc.

[0035] The content of the positive electrode active material in the positive electrode active material layer 54 is preferably 70% by mass or more, more preferably 85% by mass to 99% by mass. The content of the conductive material in the positive electrode active material layer 54 is preferably 0.1% by mass to 20% by mass, more preferably 0.3% by mass to 15% by mass. The content of the binder in the positive electrode active material layer 54 is preferably 0.4% by mass to 15% by mass, more preferably 0.5% by mass to 10% by mass.

[0036] like Figure 3 As shown, in the negative electrode sheet 60, a negative electrode active material layer 64 is formed on one or both sides (in this case, both sides) of the negative electrode current collector 62 along the long side direction. The negative electrode sheet 60 has a portion where the negative electrode active material layer 64 is not formed and the negative electrode current collector 62 is exposed, namely, the non-formed portion 62a of the negative electrode active material layer. A negative electrode current collector plate 44a is bonded to the non-formed portion 62a of the negative electrode active material layer.

[0037] Examples of negative electrode current collector 62 constituting negative electrode sheet 60 include copper foil. The negative electrode active material layer 64 contains a negative electrode active material. Examples of negative electrode active materials include carbon-based negative electrode active materials (e.g., graphite, hard carbon, soft carbon, etc.). The negative electrode active material layer 64 may contain binders (e.g., styrene-butadiene rubber (SBR), thickeners (e.g., carboxymethyl cellulose (CMC), etc.).

[0038] The graphite content in the negative electrode active material layer 64 is preferably 90% by mass or more, more preferably 95% by mass to 99% by mass. The binder content in the negative electrode active material layer 64 is preferably 0.1% by mass to 8% by mass, more preferably 0.5% by mass to 3% by mass. The thickener content in the negative electrode active material layer 64 is preferably 0.3% by mass to 3% by mass, more preferably 0.5% by mass to 2% by mass.

[0039] Examples of spacer 70 include porous resin sheets such as polyethylene and polypropylene. The porous sheet can be a single-layer or multi-layer structure. A heat-resistant layer (HRL) can be provided on the surface of spacer 70.

[0040] Non-aqueous electrolytes typically contain a non-aqueous solvent and a supporting salt (in other words, an electrolyte salt). Examples of non-aqueous solvents include carbonates (such as ethylene carbonate, methyl ethyl carbonate, dimethyl carbonate, etc.), esters, and ethers. Examples of supporting salts include lithium salts such as LiPF6. The concentration of the supporting salt is not particularly limited, but is preferably 0.7 mol / L to 1.3 mol / L. Non-aqueous electrolytes can contain various additives such as gas generators and film-forming agents. It should be noted that in this embodiment, a non-aqueous electrolyte is used as the electrolyte, but the electrolyte can be a solid electrolyte.

[0041] The lithium-ion secondary battery 100 is used, for example, as a power source for automotive applications (i.e., as a drive power source for vehicles such as battery electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs)) and electronic devices.

[0042] As mentioned above, in the positive electrode of lithium-ion secondary batteries, Li, Ni, Co, and Mn are typically used as the constituent metal elements of lithium nickel cobalt manganese composite oxides as the positive electrode active material. Al is commonly used in the positive electrode current collector. Cu is commonly used in the negative electrode current collector. Additionally, Li is used in the non-aqueous electrolyte of lithium-ion secondary batteries. Furthermore, Al can be used in the battery casing.

[0043] <Processes involved in the recycling of waste from lithium-ion secondary batteries>

[0044] according to Figure 1 The recycling of waste from lithium-ion secondary batteries is explained. Waste from lithium-ion secondary batteries includes, for example, used lithium-ion secondary batteries and defective lithium-ion secondary batteries. Typically, this waste contains Li, Ni, Co, Mn, and O from the positive electrode active material; Al from the positive electrode current collector; C from the negative electrode active material; Cu from the negative electrode current collector; Li from the non-aqueous electrolyte; and Al from the battery casing as main elements. It should be noted that waste from lithium-ion secondary batteries can also be waste from components such as the electrode body. As will be explained later... Figure 1 The metallic elements recorded in the text can be in the form of oxides, carbonates, etc.

[0045] like Figure 1As shown, the recycling (i.e., recycling method) includes: a crushing step S10, which crushes the waste from lithium-ion secondary batteries; a sorting step S20, which sorts the crushed material obtained from the crushing step S10 to remove metal fragments; a roasting step S30, which reduces and roasts the black substance obtained from the sorting step S20; a first ammonia leaching step S40, which leaches ammonia from the roasted black substance obtained from the roasting step S30 to remove Cu; and a second ammonia leaching step S50, which leaches ammonia from the solid residue obtained from the first ammonia leaching step S40 to obtain a substance containing Ni. 2+ Co 2+ Mn 2+ NH3, NH4 + CO3 2- The leachate. Additionally, the recovery includes: a crystallization step S110, in which the leachate is used as a feed solution and added to a precipitation solution to precipitate carbonates containing Ni, Co, and Mn.

[0046] <Crushing Process S10>

[0047] In this recycling process, a crushing step S10 is performed to shred the waste from lithium-ion secondary batteries. The crushing step S10 can be carried out using known methods. For example, known crushing devices such as crushers, pulverizers, and shredders can be used to shred the waste from lithium-ion secondary batteries. This yields shredded waste from lithium-ion secondary batteries.

[0048] Here, in the crushing process S10, the waste lithium-ion secondary batteries may not be completely crushed. For example, the battery casing of the lithium-ion secondary battery can be opened and the electrode body removed, and only the electrode body can be crushed. In this case, the constituent materials of the battery casing can be effectively removed.

[0049] It should be noted that pretreatment of lithium-ion secondary battery waste can be performed before the crushing step S10. For example, a discharge treatment step can be performed to discharge the lithium-ion secondary battery waste before the crushing step S10. This allows for safer recycling of lithium-ion secondary battery waste. The discharge treatment can be performed according to known methods.

[0050] <Sorting Process S20>

[0051] Next, in this recycling process, a sorting step S20 is performed, which involves sorting the aforementioned fragments to remove metal fragments. Typical examples of metal fragments are fragments of the battery casing, fragments of the positive electrode current collector, and fragments of the negative electrode current collector. Typically, fragments of the battery casing contain Al, fragments of the positive electrode current collector contain Al, and fragments of the negative electrode current collector contain Cu.

[0052] The sorting process S20 can be carried out according to known methods. Specifically, for example, the crushed material can be screened to remove metal fragments. Alternatively, magnetic separation can be performed based on the material of the metal fragments.

[0053] By implementing the sorting step S20, most of the Al and Cu contained in the waste can be removed. Therefore, in the sorting step S20, it is preferable to remove at least Al and Cu contained in the waste.

[0054] After removing the metal fragments, a black powder is typically obtained. This black powder is called black substance. Therefore, black substance is obtained by performing a sorting process S20. The metal elements contained in the black substance are typically Li, Ni, Co, Mn, Al, Cu, etc. Ni, Co, and Mn typically come from the positive electrode active material and are in the form of composite oxides. Al and Cu come from metal fragments that were not completely removed in the sorting process S20. In addition, the black substance typically contains carbon (C) from the negative electrode active material, etc.

[0055] <Roasting process S30>

[0056] Next, in this recycling process, a roasting step S30 is performed to reduce and roast the black material. Here, reduction roasting refers to roasting that reduces at least a portion of the metal in the metal oxide contained in the black material. In particular, Ni and Co contained in the black material in the form of composite oxides are reduced to metal in the roasting step.

[0057] Such roasting is typically carried out in an atmosphere with an oxygen concentration of 5% by volume or less. The oxygen concentration in this atmosphere is preferably 1% by volume or less. As the atmosphere, an inert gas atmosphere such as argon or nitrogen is particularly preferred.

[0058] The roasting temperature is, for example, 650℃ to 1500℃, preferably 750℃ to 1000℃. The roasting time can be appropriately selected according to the roasting temperature, for example, 1 hour to 24 hours, preferably 4 hours to 12 hours.

[0059] By performing the roasting process S30, a roasted black substance can be obtained. The roasted black substance typically contains Li, Ni, Co, Mn, Al, Cu, and C. Li is typically in the form of Li₂CO₃. Mn is typically in the form of MnO. Ni, Co, Al, and Cu are typically in their metallic forms.

[0060] Here, among the components contained in the calcined black material, Li2CO3 has particularly high solubility in water. Therefore, in this recycling process, a water leaching process can be implemented to remove Li2CO3 from the calcined black material by contacting it with water.

[0061] If the calcined black substance is brought into contact with water, the Li₂CO₃ contained in the calcined black substance will preferentially dissolve in the water. Therefore, Li₂CO₃ can preferentially move into the aqueous phase, thus removing Li₂CO₃ from the calcined black substance.

[0062] The water leaching process can be carried out according to known methods. Specifically, for example, it can be carried out by immersing the roasted black substance in water and stirring appropriately. Leaching can be carried out at room temperature or under heating.

[0063] <First Ammonia Leaching Process S40>

[0064] In this recycling process, a first ammonia leaching step S40 is performed to remove Cu from the roasted black material by ammonia leaching.

[0065] In the first ammonia leaching step S40, the calcined black substance is leached with ammonia, therefore a first ammonia solution containing at least water and ammonia is used as the leaching agent. The first ammonia solution may contain only water and ammonia, or it may contain other components. Ammonium carbonate is an example of such other components. When the first ammonia solution contains ammonium carbonate, the leaching rate of Cu can be further increased.

[0066] It should be noted that, as mentioned above, Li2CO3 has particularly high solubility in water, and also high solubility in the first ammonia solution. Therefore, even if the above-mentioned water leaching process is not performed, and if Li2CO3 remains in the calcined black material after the water leaching process, Li2CO3 can also be removed from the calcined black material by ammonia leaching in the first ammonia leaching process S40.

[0067] The concentration of ammonia in the first ammonia solution is not particularly limited as long as it is sufficient to leach Cu. From the viewpoint of suppressing the dissolution of metals other than Cu and Li, the concentration of ammonia in the first ammonia solution is preferably 0.01% by mass or more, more preferably 0.1% by mass or more. Furthermore, the upper limit of the ammonia concentration is preferably 5% by mass or less, more preferably 2% by mass or less. From the viewpoint of leaching capacity and ease of processing, the ammonia concentration is particularly preferably 0.1% to 2% by mass.

[0068] The amount of ammonium carbonate in the first ammonia solution is preferably 0.5 to 1.5 moles of the amount of Cu contained in the calcined black material, more preferably 0.8 to 1.2 moles, and even more preferably equimolar. On the other hand, ammonium carbonate promotes the leaching of Ni and Co. The amount of ammonium carbonate in the first ammonia solution is preferably 0.20 moles or less of the total amount of Ni and Co contained in the calcined black material, more preferably 0.10 moles or less, and even more preferably 0.05 moles or less.

[0069] There is no particular limitation on the amount of ammonia solution used in the first ammonia solution; it can be the same as the amount used in the well-known ammonia leaching method. For example, the amount of the first ammonia solution used is the amount that completely submerges the roasted black substance.

[0070] Typically, oxygen participates in the dissolution of Cu in ammonia solution. The first ammonia leaching step S40 can be carried out in the atmosphere using atmospheric oxygen. However, from the viewpoint of a high dissolution rate, it is preferable to supply oxygen to the first ammonia solution during leaching. As for the amount of oxygen supplied, it is preferable to supply an excess of the target oxidizing element (i.e., Cu) contained in the calcined black material.

[0071] Oxygen is preferably supplied by introducing an oxygen-containing gas (such as oxygen gas, atmosphere, etc.) into the first ammonia solution through bubbling or similar means. Oxygen can also be supplied by sealing a container and simultaneously introducing an oxygen-containing gas into it while pressurizing it.

[0072] The first ammonia leaching process S40 can be performed as follows: Prepare a container equipped with heating mechanisms such as heaters, temperature measuring mechanisms such as thermometers and temperature sensors, stirring mechanisms such as stirring blades and magnetic stirring rods, as needed. Additionally, prepare a bubbling device as needed.

[0073] Add the calcined black substance and the first ammonia solution to the container. If necessary, use a bubbling device to supply oxygen-containing gas into the first ammonia solution in the form of bubbles.

[0074] The leaching temperature is not particularly limited, but is preferably above 0°C and below 80°C, more preferably 10°C to 50°C, and even more preferably 15°C to 35°C. The leaching time is not particularly limited, for example, from 0.5 hours to 48 hours, preferably from 1 hour to 24 hours, and even more preferably from 1.5 hours to 12 hours. Stirring is preferably performed during ammonia leaching. The stirring speed is not particularly limited, but is for example from 200 rpm to 2000 rpm, preferably from 300 rpm to 1000 rpm, and even more preferably from 400 rpm to 800 rpm.

[0075] Ammonia leaching can be completed by solid-liquid separation such as filtration. During ammonia leaching, Cu and Li selectively move into the aqueous phase. Therefore, through this solid-liquid separation, as... Figure 1 As shown, it is possible to obtain a product containing Cu. 2+ And may contain Li + Aqueous phase (i.e., containing Cu) 2+ And may contain Li + The first ammonia leaching step S40 can be carried out, comprising an aqueous ammonia solution and solid residues containing Ni, Co, Mn, Al, and C.

[0076] Here, in the first ammonia leaching step S40, during ammonia leaching, insoluble precipitates sometimes form on the surface of the calcined black material. These insoluble precipitates are believed to be compounds containing Ni, Co, and Cu. These insoluble precipitates can be removed by ammonia leaching under low oxygen concentration conditions.

[0077] Therefore, in one embodiment of the first ammonia leaching step S40, the first ammonia leaching step S40 can leach the calcined black substance using a first ammonia aqueous solution (A) with a concentration of 2.5 mol / L or less in the presence of oxygen, and leach the resulting solid residue using a first ammonia aqueous solution (B) in an inactive gas atmosphere. According to this embodiment, the Cu recovery rate becomes particularly high. As for leaching in the presence of oxygen, it is preferable to leach while supplying a gas (e.g., atmosphere, preferably oxygen) with an oxygen concentration of 21% by volume or more into the container containing the first ammonia aqueous solution (A). As for the method of supplying the gas, it is preferable to bubble the gas into the solution.

[0078] In this embodiment, oxygen is preferably supplied to the container containing the first ammonia solution (A). An inert gas (e.g., nitrogen) is preferably supplied to the container containing the first ammonia solution (B). As a supply method, bubbling the gas into the solution is preferred. The concentration of the first ammonia solution (A) is preferably 0.1 mol / L to 1.0 mol / L. The concentration of the first ammonia solution (B) is preferably 5 mol / L or more, more preferably 10 mol / L to 16.0 mol / L. Leaching using the first ammonia solution (A) and leaching using the first ammonia solution (B) can be repeated.

[0079] It should be noted that by evaporating ammonia from the aqueous phase obtained in the first ammonia leaching process, Cu can be... 2+ CuO is precipitated and recovered. When ammonia is evaporated after adding a hydroxide (e.g., lithium hydroxide) to the aqueous phase, Cu can be recovered as Cu(OH)₂. 2+ At this point, even with the ammonia evaporated, the lithium component remains dissolved in the aqueous phase, thus Cu and Li can be separated by solid-liquid separation.

[0080] The evaporation of ammonia can be carried out using known methods. For example, ammonia can be evaporated by adding an aqueous phase into an open container and heating it with stirring. The heating temperature is preferably 50°C or higher, more preferably 70°C or higher, and even more preferably 90°C or higher. The heating temperature can be lower than the boiling point of water (i.e., 100°C). The heating time is, for example, 0.5 hours to 24 hours, preferably 2 hours to 12 hours. The stirring speed is 200 rpm to 2000 rpm, preferably 400 rpm to 800 rpm.

[0081] The evaporated ammonia can be recovered using known ammonia capture devices. The recovered ammonia can then be reused in processes that utilize ammonia in the recycling of waste from lithium-ion secondary batteries.

[0082] It should be noted that in the roasting process S30, Li is obtained in the form of LiCl when chlorine is mixed in the roasting atmosphere, and in the form of LiOH when hydrogen is mixed in the roasting atmosphere. In this case, these lithium compounds also have high solubility in water, so the first ammonia leaching process S40 can be performed in the same way.

[0083] <Second Ammonia Leaching Process S50>

[0084] In this recycling process, the solid residue obtained in the first ammonia leaching step S40 is subjected to ammonia leaching to obtain a product containing Ni. 2+ Co 2+ Mn 2+ NH3, NH4 + CO3 2- The second ammonia leaching process S50 of the leachate.

[0085] In the second ammonia leaching step S50, a second ammonia aqueous solution containing ammonia (NH3) and ammonium carbonate ((NH4)2CO3) is used as the leaching agent so that the resulting leaching solution contains NH3 and NH4. + and CO3 2- This leaching agent allows for the preferential leaching of Ni, Co, and Mn. The second ammonia solution may contain only water, ammonia, and ammonium carbonate, or it may contain other components in addition to these.

[0086] In the second ammonia solution, the concentration of ammonia is not particularly limited, and can be, for example, 1% by mass or more and a saturation concentration (i.e., about 35% by mass) or less. The concentration of ammonia in the second ammonia solution is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more. From the viewpoint of leaching capacity and ease of processing, the concentration of ammonia is particularly preferably 15% to 25% by mass.

[0087] Ammonium carbonate functions as a pH adjuster. The amount of ammonium carbonate in the second ammonia solution is preferably such that the pH (25°C) of the second ammonia solution is 9–12, more preferably 10–11. The concentration of ammonium carbonate in the second ammonia solution is preferably 0.5 mol / L to 3 mol / L, more preferably 1 mol / L to 3 mol / L, and even more preferably 1.5 mol / L to 2.5 mol / L.

[0088] There is no particular limitation on the amount of ammonia solution used in the second ammonia solution; it can be the same as the amount used in the well-known ammonia leaching method. For example, the amount of the second ammonia solution used can be the amount that completely submerges the object.

[0089] Here, ammonia leaching in the second ammonia leaching step S50 can be performed while gas is being supplied to the second ammonia solution. In this case, the leaching selectivity of Ni, Co, and Mn varies with the oxygen concentration contained in the gas. Specifically, the higher the oxygen concentration of the supplied gas, the more preferentially Ni and Co are leached. On the other hand, the lower the oxygen concentration of the supplied gas, the more preferentially Mn is leached.

[0090] The second ammonia leaching process S50 can be carried out as follows: Prepare a container equipped with heating mechanisms such as heaters, temperature measuring mechanisms such as thermometers and temperature sensors, stirring mechanisms such as stirring blades and magnetic stirring rods, as needed. Additionally, prepare a bubbling device as needed.

[0091] Solid residue and a second ammonia solution are added to the container. Gas is supplied to the container containing the second ammonia solution as needed. Preferably, a bubbling device is used to supply gas to the second ammonia solution in the form of bubbles.

[0092] The second ammonia leaching step S50 can be carried out at room temperature (i.e., 25±10°C) or under heating. The leaching temperature is preferably above 0°C and below 80°C. More preferably, it is 10°C to 50°C, and even more preferably, it is 15°C to 35°C.

[0093] The leaching time can be appropriately determined based on the leaching temperature. The higher the leaching temperature, the shorter the leaching time can be. The leaching time is, for example, 1 hour or more, preferably 2 hours or more, and more preferably 4 hours or more. On the other hand, from the viewpoint of operational efficiency, the leaching time is, for example, 48 hours or less, preferably 24 hours or less, and more preferably 10 hours or less.

[0094] Stirring is preferably performed during leaching. The stirring speed is not particularly limited, but is preferably 200 rpm or higher, more preferably 400 rpm or higher, and even more preferably 500 rpm or higher. The stirring speed can be 2000 rpm or lower, 1000 rpm or lower, or 800 rpm or lower.

[0095] Ammonia leaching can be completed by solid-liquid separation such as filtration. During ammonia leaching, Ni, Co, and Mn selectively move into the aqueous phase. Therefore, through this solid-liquid separation, such as... Figure 1 As shown, a leachate containing Ni ions, Co ions, Mn ions, ammonia, ammonium ions, and carbonate ions (i.e., a second ammonia aqueous solution containing Ni ions, Co ions, Mn ions, ammonia, ammonium ions, and carbonate ions) and a solid residue containing Al and C can be obtained. The second ammonia leaching step S50 can be performed as described above. This leachate can be used as a feed solution containing Ni ions, Co ions, Mn ions, ammonia, ammonium ions, and carbonate ions in the crystallization step S110.

[0096] Here, as described above, when ammonia leaching is performed while gas is supplied to a container containing a second ammonia solution, the leaching selectivity of Ni, Co, and Mn varies with the oxygen concentration contained in the gas. Therefore, in the second ammonia leaching step S50, by performing leaching in two or more stages with varying types of supplied gas, all of Ni, Co, and Mn can be obtained with high recovery rates.

[0097] As one specific embodiment, the second ammonia leaching process S50 includes: a Mn leaching process, in which a second ammonia aqueous solution (A) is used to leach solid residue, thereby leaching Mn into a first aqueous phase; and a Ni and Co leaching process, in which a second ammonia aqueous solution (B) is used to leach solid residue obtained in the Mn leaching process, thereby leaching Ni and Co into a second aqueous phase. Here, the dissolved oxygen content in the second ammonia aqueous solution (A) used in the Mn leaching process is less than the dissolved oxygen content in the second ammonia aqueous solution (B) used in the Ni and Co leaching process.

[0098] In this embodiment, Mn can be recovered at a high recovery rate in the first aqueous phase during the Mn leaching process, and Ni and Co can be recovered at a high recovery rate in the second aqueous phase during the Ni and Co leaching process. Furthermore, by combining the first and second aqueous phases, a leachate containing Ni ions, Co ions, Mn ions, ammonia, ammonium ions, and carbonate ions can be obtained, which can be used as the feed solution for the crystallization process S110.

[0099] The second ammonia solution (A) used in the Mn leaching process and the second ammonia solution (B) used in the Ni and Co leaching processes are equivalent to the aforementioned second ammonia solution; they may have the same composition or different compositions. From a management perspective, it is advantageous for the second ammonia solution (A) and the second ammonia solution (B) to have the same composition.

[0100] In the Mn leaching process, leaching is preferably carried out while supplying a gas with an oxygen concentration of 21% by volume or less into a container containing a second ammonia solution (A), so that the dissolved oxygen content in the second ammonia solution (A) during the Mn leaching process is less than the dissolved oxygen content in the second ammonia solution (B) during the Ni and Co leaching processes. The oxygen concentration of the supplied gas is preferably 18% by volume or less, more preferably 5% by volume or less, and even more preferably 1% by volume or less. The gas supplied in the Mn leaching process is particularly preferably an inert gas (e.g., nitrogen, argon, etc.). Bubbling is preferred as the method of supplying this gas.

[0101] In the Ni and Co leaching process, leaching is preferably carried out while supplying a gas with an oxygen concentration of 50% by volume or more into a container containing a second ammonia solution (B), so that the dissolved oxygen content in the second ammonia solution (A) during the Mn leaching process is less than the dissolved oxygen content in the second ammonia solution (B) during the Ni and Co leaching process. The oxygen concentration of the supplied gas is preferably 60% by volume or more, more preferably 90% by volume or more, and particularly preferably 99% by volume or more. The gas supplied in the Ni and Co leaching process is particularly preferably oxygen. Bubbling is preferred as the method of supplying this gas. Regarding the amount of gas supplied in the Ni and Co leaching process, the amount of oxygen supplied is preferably equimolar or more relative to the total amount of Ni and Co, more preferably 2 to 100 molar times, and even more preferably 3 to 100 molar times.

[0102] As a step in this embodiment, the solid residue is leached using a gas with a specified oxygen concentration and a second ammonia aqueous solution (A), followed by solid-liquid separation to obtain a leachate and a solid residue. This performs the Mn leaching process. The obtained solid residue is leached using a gas with a specified oxygen concentration and a second ammonia aqueous solution (B), followed by solid-liquid separation to obtain a leachate and a solid residue. This performs the Ni and Co leaching process. The leachate obtained in the Mn leaching process is mixed with the leachate obtained in the Ni and Co leaching process.

[0103] <Crystallization process S110>

[0104] In the crystallization process S110, Ni ions (Ni 2+ ), Co ions (Co 2+ Mn ions (Mn 2+ ), ammonia (NH3), ammonium ions (NH4) + ) and carbonate ions (CO3) 2- The feed solution is added to the precipitation solution where the ammonia concentration is lower than that of the feed solution.

[0105] The feed solution is typically an aqueous solution. Preferably, the feed solution comprises a liquid generated from the recycling of waste from lithium-ion secondary batteries. This liquid is typically an ammonia leachate containing at least one of Ni, Co, and Mn. In particular, the leachate obtained in the second ammonia leaching step S50 described above can be used as the feed solution. However, the feed solution is not limited to this.

[0106] For example, the feed solution is an aqueous solution obtained by dissolving a water-soluble salt of Mn in an ammonia leachate containing Ni, Co, ammonia, and ammonium carbonate, which is obtained through other recycling methods for the waste from lithium-ion secondary batteries described above. For example, the feed solution is an aqueous solution obtained by adding at least one of a water-soluble salt of Ni, a water-soluble salt of Co, and a water-soluble salt of Mn to the leachate obtained in the second ammonia leaching step S50, and adjusting the molar ratio of Ni, Co, and Mn. Alternatively, for example, the feed solution is an aqueous solution obtained by dissolving a water-soluble salt of Ni, a water-soluble salt of Co, a water-soluble salt of Mn, ammonia, and ammonium carbonate in water.

[0107] From the viewpoint of preventing the precipitation of Ni, Co, and Mn during storage, the pH of the feed solution at 25°C is preferably in the range of 10.0–12.0. The pH of the feed solution at 25°C can be adjusted by the release of Ni ions, Co ions, Mn ions, ammonia (NH3), and ammonium ions (NH4) from the feed solution. + ) and carbonate ions (CO3) 2- Adjust the amount or concentration of ( ).

[0108] Therefore, the Ni ions, Co ions, Mn ions, ammonia (NH3), and ammonium ions (NH4) in the feed solution + The amount or concentration of the raw material solution is preferably the amount or concentration of the raw material solution with pH within the above range.

[0109] The molar ratio of Ni, Co, and Mn in the feed solution can be the same as the desired molar ratio of the positive electrode active material to be manufactured. The amount of carbonate ions in the feed solution is not particularly limited, but it is preferably at least 1 molar multiple, more preferably at least 1.5 molar multiples, relative to the total of Ni, Co, and Mn. It should be noted that even if the amount of carbonate ions in the feed solution is less than 1 molar multiple relative to the total of Ni, Co, and Mn, the crystallization step S110 can still be performed by including carbonate ions in the precipitation solution.

[0110] The precipitating solution functions by precipitating Ni, Co, Mn, and carbonate ions contained in the feed solution as a complex carbonate containing Ni, Co, and Mn (i.e., nickel-cobalt-manganese complex carbonate) when the feed solution is added. Therefore, the ammonia concentration in the precipitating solution is lower than that in the feed solution.

[0111] There are no particular limitations on the precipitating solution as long as the ammonia concentration is lower than that of the feed solution. The precipitating solution can be an ammonium ion donor. Therefore, for example, the precipitating solution can be an aqueous solution of ammonium salts such as ammonium carbonate, ammonium sulfate, or ammonium chloride. Ammonium carbonate is preferred because it consists only of components present in the feed solution (i.e., it does not contain impurities) and can supply carbonate ions to promote carbonate precipitation. Alternatively, water (e.g., ion-exchanged water, distilled water, etc.) can be used as the precipitating solution. Using water makes preparation of the precipitating solution easier and is also cost-effective.

[0112] In the feed solution, Ni, Co, and Mn ions form ammonia complexes with ammonia and ammonium ions, respectively, thus maintaining a stable state for Ni, Co, and Mn. Here, evaporating ammonia from the feed solution induces crystallization reactions of Ni, Co, and Mn. However, among the Ni, Co, and Mn complexes, the Mn complex is the least stable. Therefore, a large amount of Mn precipitates in the initial stage of the crystallization reaction, while a small amount precipitates in the later stage. As a result, the proportion of Mn is higher in the center of the precipitated carbonate particles and lower on the surface. Consequently, uneven distribution of Mn occurs in the center of the carbonate particles. This is because the ammonia concentration changes slowly when ammonia is evaporated from the feed solution.

[0113] In the manufacturing method disclosed herein, the ammonia concentration in the precipitation solution is lower than that in the feed solution. Therefore, when the feed solution is added to the precipitation solution, the ammonia concentration near the ammonia complex decreases sharply, and all Ni, Co, and Mn complexes in the feed solution become unstable. Consequently, Ni, Co, and Mn all precipitate at the same rate. As a result, the uneven distribution of Mn at the center of the precipitated carbonate particles is suppressed.

[0114] From the viewpoint of effectively performing this function, as a reference value for ammonia concentration, the pH of the precipitation solution at 25°C is preferably less than 10.0, more preferably less than 9.5, further preferably less than 9.0, and particularly preferably less than 8.0. There is no particular limitation on the lower limit of the pH of the precipitation solution at 25°C. When water is used as the precipitation solution, atmospheric carbon dioxide dissolves into the water, thereby lowering the pH to around 5.2. Taking this into consideration, the lower limit of the pH of the precipitation solution at 25°C can be 5.2 or higher, preferably 6.5 or higher, and more preferably 7.0 or higher.

[0115] Crystallization can be performed as follows: Prepare a known reaction vessel for crystallization. This reaction vessel may be equipped with a heating mechanism such as a heater, a temperature measuring mechanism such as a thermometer and temperature sensor, a pH measuring mechanism such as a pH meter, stirring blades, a magnetic stirring rod, etc.

[0116] A precipitation solution is added to the reaction tank. Then, a feed solution is added to the precipitation solution. From the viewpoint of increasing the change in ammonia concentration, it is preferable to add the feed solution dropwise to the precipitation solution. By adding the feed solution dropwise to the precipitation solution, a reaction solution is formed within the reaction tank.

[0117] The pH of the reaction solution during crystallization is preferably 10.0 or lower, more preferably 9.5 or lower, at 25°C. Therefore, it is preferable to adjust the amount and addition rate of the raw material solution in such a way that the pH of the reaction solution does not exceed the above-mentioned range.

[0118] The crystallization temperature is not particularly limited as long as the crystallization reaction occurs. Crystallization can be carried out at room temperature (i.e., 25°C ± 10°C) or under heating. The crystallization temperature is preferably 45°C or higher, more preferably 60°C or higher, and even more preferably 80°C or higher. On the other hand, the crystallization temperature can be lower than the boiling point of the reaction solution or lower than 100°C.

[0119] Stirring is preferably performed during crystallization. The stirring speed is not particularly limited, but is preferably 200 rpm or higher, more preferably 400 rpm or higher, and even more preferably 600 rpm or higher. The stirring speed can be 2000 rpm or lower, 1000 rpm or lower, or 800 rpm or lower.

[0120] The crystallization time is not particularly limited and can be appropriately determined based on the leaching temperature, stirring speed, etc. For example, the crystallization time is 10 minutes or more, preferably 1 hour or more, and more preferably 2 hours or more. From the viewpoint of operational efficiency, the crystallization time is, for example, 48 hours or less, preferably 24 hours or less, more preferably 12 hours or less, and even more preferably 6 hours or less.

[0121] Carbonates containing Ni, Co, and Mn can be precipitated by crystallization. The precipitated carbonates containing Ni, Co, and Mn can be recovered using known methods. For example, the precipitated carbonates containing Ni, Co, and Mn can be separated from the aqueous phase by solid-liquid separation such as filtration, washed with water, and dried, thereby recovering the carbonates containing Ni, Co, and Mn.

[0122] The aqueous phase after solid-liquid separation contains ammonia and unreacted ammonium carbonate. This aqueous phase can be adjusted in terms of composition, pH, etc., for reuse in processes that recover ammonia and ammonium carbonate from waste materials used in lithium-ion secondary batteries. Alternatively, ammonia and ammonium carbonate can be recovered from this aqueous phase and reused in processes that recover ammonia from waste materials used in lithium-ion secondary batteries and processes that use ammonium carbonate.

[0123] As described above, through the crystallization process S110, a carbonate containing Ni, Co, and Mn (i.e., nickel-cobalt-manganese composite carbonate) can be obtained as a precursor for the positive electrode active material. This carbonate can be used in the manufacture of the positive electrode active material for lithium-ion secondary batteries. The following is a detailed explanation.

[0124] <Method for Manufacturing Positive Electrode Active Material>

[0125] The method for manufacturing the positive electrode active material includes: a step of obtaining a precursor by the method for manufacturing a precursor of the positive electrode active material disclosed above (hereinafter also referred to as the "precursor preparation step"), a step of mixing the precursor with a lithium compound to obtain a mixture (hereinafter also referred to as the "mixing step"), and a step of calcining the mixture (hereinafter also referred to as the "calcination step").

[0126] The method for manufacturing this positive electrode active material will be described in detail. The precursor preparation process is as described above in the method for manufacturing the precursor of the positive electrode active material disclosed herein.

[0127] Prior to the mixing process, the precursor can be heat-treated. At this time, the precursor can be converted into an oxide. The composite oxide containing Ni, Co, and Mn also serves as a precursor for the positive electrode active material. When converting to an oxide, the heat treatment temperature is preferably 300°C to 1000°C. The heat treatment time is preferably 1 hour or more, more preferably 1 hour to 48 hours, and even more preferably 5 hours to 24 hours. The heat treatment can be performed in atmospheric air.

[0128] The lithium compound used in the mixing process becomes the Li source for the positive electrode active material. Examples of lithium compounds include lithium carbonate, lithium nitrate, and lithium hydroxide, which are converted into oxides through calcination.

[0129] The mixing ratio of the lithium compound and the precursor can be appropriately determined according to the desired composition of the positive electrode active material. For example, in the positive electrode active material, the ratio of Li to metals other than Li (usually the sum of Ni, Co, and Mn) is preferably 0.95 to 1.15. Therefore, it is preferable to mix the lithium compound and the precursor in such a way that the molar ratio of Li contained in the lithium compound to the metals contained in the precursor (usually the sum of Ni, Co, and Mn) is 0.95 to 1.15.

[0130] If it is desired to introduce a metal other than Li (also known as other metals) not included in the precursor into the positive electrode active material, other metal sources can be further mixed in according to known methods.

[0131] The mixing of the lithium compound and the precursor can be carried out according to known methods. For example, the precursor and lithium compound can be mixed using mixing devices such as shaking mixers, V-type mixers, belt mixers, Julia mixers, and Loedige mixers. A mixture is thus obtained.

[0132] The calcination process can be carried out using known methods. For example, the calcination of the mixture can be performed using a known electric furnace or the like. From the viewpoint of suppressing oxygen defects in the positive electrode active material, an oxidizing atmosphere is preferred as the calcination atmosphere. The oxidizing atmosphere is preferably an atmosphere with an oxygen concentration of 10% by volume or more, which can be an atmospheric atmosphere or an oxygen atmosphere (i.e., an atmosphere with an oxygen concentration higher than that of the atmosphere). The calcination temperature is, for example, 650°C to 1000°C, preferably 700°C to 900°C. The calcination time is, for example, 3 hours to 8 hours, preferably 3.5 hours to 7.5 hours.

[0133] As described above, lithium nickel cobalt manganese composite oxides can be manufactured as positive electrode active materials. These positive electrode active materials can be used in lithium-ion secondary batteries according to known methods.

[0134] The following describes in detail embodiments relating to this disclosure, but it is not intended to limit this disclosure to the contents shown in these embodiments.

[0135] [Preparation of raw material solution]

[0136] Ni metal, Co metal, and Mn oxide were dissolved in an aqueous solution of ammonium carbonate. The molar ratio of Ni, Co, and Mn was 90:5:5. The amount of ammonium carbonate was 1.5 moles relative to the total amount of Ni and Co. The ammonium concentration of the aqueous solution was 13 mol / L. The resulting solution was used as the feed solution. The pH of the feed solution at 25°C was determined to be 11 by the following method.

[0137] [pH Measurement]

[0138] In the examples and comparative examples, the pH of each solution was measured using a commercially available pH meter (Horiba Seisakusho Co., Ltd. benchtop pH meter "F-71S").

[0139] [Comparative Example 1]

[0140] The above-mentioned raw material solution was added to a reaction tank. Heating was carried out to 80°C, with ammonia evaporated while stirring, to induce crystallization. Small samples of the crystals and reaction solution were taken at regular intervals, and the pH of the reaction solution at 25°C was measured after cooling. Heating was stopped when the pH fluctuation in the reaction tank decreased. At this point, the pH after crystallization was 9.3. Solid-liquid separation was then performed by filtration, and the crystals were obtained by washing with water.

[0141] [Example 1]

[0142] Prepare an aqueous solution of ammonium carbonate with a pH of 9.0 at 25°C as the precipitation solution. Add this solution to the reaction tank. Heat the precipitation solution to 80°C, and while stirring, add the above-mentioned raw material solution dropwise to the precipitation solution to carry out the crystallization reaction. Take small samples of the crystals and reaction solution at regular intervals, and after cooling, measure the pH of the reaction solution at 25°C. Stop adding the raw material solution and heating when the pH of the reaction solution in the reaction tank rises to 10.7. At this point, the pH after crystallization is 10.7. Then, perform solid-liquid separation by filtration, and wash with water to obtain the crystals.

[0143] [Example 2]

[0144] The dropping rate of the feed solution was adjusted to prevent the pH of the reaction solution in the reaction tank from rising during the reaction. The dropping and heating of the feed solution were stopped when the pH of the reaction solution in the reaction tank rose to 9.4. Otherwise, crystals were obtained in the same manner as in Example 1.

[0145] [Example 3]

[0146] Prepare pure water at pH 7.0 at 25°C as the precipitation solution. Add this water to the reaction tank. Heat the precipitation solution to 80°C, and while stirring, add the above-mentioned raw material solution dropwise into the precipitation solution. Stop adding the raw material solution and heating when the pH of the reaction solution in the reaction tank rises to 10.5. Then, perform solid-liquid separation by filtration, and wash with water to obtain the crystals.

[0147] [Example 4]

[0148] The dropping rate of the feed solution was adjusted to prevent the pH of the reaction solution in the reaction tank from rising during the reaction. The dropping and heating of the feed solution were stopped when the pH of the reaction solution in the reaction tank rose to 9.2. Otherwise, crystals were obtained in the same manner as in Example 3.

[0149] [Example 5]

[0150] The temperature inside the reaction tank was set to 90°C, and otherwise, crystals were obtained in the same manner as in Example 4.

[0151] [Example 6]

[0152] The temperature inside the reaction tank was set to 70°C, and otherwise, crystals were obtained in the same manner as in Example 4.

[0153] [Example 7]

[0154] The temperature inside the reaction tank was set to 60°C, and otherwise, crystals were obtained in the same manner as in Example 4.

[0155] [Example 8]

[0156] The temperature inside the reaction tank was set to 45°C. The addition and heating of the raw material solution were stopped when the pH of the reaction solution in the reaction tank rose to 9.4. Otherwise, crystals were obtained in the same manner as in Example 4.

[0157] [Evaluation of Mn segregation rate]

[0158] Following conventional methods, samples were prepared to expose the particle cross-sections of the crystals obtained in Comparative Example 1 and each embodiment. The samples were observed using a scanning electron microscope (SEM), and particles with a diameter of several μm were selected. Energy-dispersive X-ray spectroscopy (EDS) was used to analyze the central and surface portions of the selected particles to determine the Mn content ratio in each portion. The ratio of Mn content in the central portion to Mn content in the surface portion was calculated for 10 particles, and the average value was taken as the Mn segregation ratio. The results are shown in Table 1. It should be noted that the Mn segregation ratio is 1.0 when Mn is not uniformly distributed. Additionally, for reference, particle cross-section images, Mn mapping images of particle cross-sections, and Ni mapping images of particle cross-sections from Comparative Example 1 are shown in Table 1. Figures 4-6 Additionally, the particle cross-sectional image, the Mn mapping image of the particle cross-section, and the Ni mapping image of the particle cross-section from Example 4 are shown respectively. Figures 7-9 .

[0159]

[0160] like Figures 4-6 As shown in Table 1, in Comparative Example 1 where carbonates were precipitated by evaporating ammonia, Mn was unevenly distributed in the center of the particles, and its proportion (Mn presence ratio in the center / Mn presence ratio in the surface layer) was extremely high, at 90.9%.

[0161] On the other hand, such as Figures 7-9 As shown in Table 1, in Examples 1-8 where carbonates were precipitated by adding the feed solution dropwise to a precipitation solution with a lower ammonia concentration than the feed solution, the uneven distribution of Mn at the center of the particles could be suppressed. Furthermore, a comparison between Example 1 and Example 2 shows that when the feed solution is added dropwise in a manner that does not raise the pH during crystallization, the crystallization reaction is carried out under conditions where the ammonia evaporation rate is sufficiently fast, thus further suppressing the uneven distribution of Mn. Moreover, a comparison between Example 2 and Example 4 shows that a lower pH in the precipitation solution further suppresses the uneven distribution of Mn. This is believed to be because, since there is no ammonia source in the precipitation solution within the reaction tank, the ammonia concentration around the ammonia complexes of Ni, Co, and Mn in the feed solution decreases sharply, making all ammonia complexes unstable, resulting in the precipitation of Ni, Co, and Mn at the same rate.

[0162] The results above show that the method for manufacturing the precursor of the positive electrode active material disclosed herein can suppress the uneven distribution of Mn in the center of the particle.

[0163] The specific examples of this disclosure have been described in detail above, but these are merely illustrative and do not limit the scope of patent protection. The technology described in the scope of patent protection includes technologies that have undergone various modifications and alterations to the specific examples described above.

[0164] That is, the method for manufacturing the precursor of the positive electrode active material and the method for manufacturing the positive electrode active material disclosed herein are the following items [1] to [9].

[0165] [1] A method for manufacturing a precursor of a positive electrode active material includes the following steps: adding a raw material solution containing Ni, Co, Mn, ammonia, ammonium ions and carbonate ions to a precipitation solution to precipitate carbonates containing Ni, Co and Mn.

[0166] The concentration of ammonia in the above-mentioned precipitate is lower than the concentration of ammonia in the above-mentioned raw material solution.

[0167] [2] According to the manufacturing method described in item [1], wherein the pH of the above-mentioned raw material liquid is 10.0 to 12.0 at 25°C, and the pH of the above-mentioned precipitate liquid is less than 10.0 at 25°C.

[0168] [3] According to the manufacturing method described in item [2], wherein the pH of the above-mentioned precipitate solution is below 9.5 at 25°C.

[0169] [4] According to the manufacturing method described in item [2], wherein the pH of the above-mentioned precipitate solution is below 8.0 at 25°C.

[0170] [5] The manufacturing method according to any one of [1] to [4], wherein the precipitating liquid is water or an aqueous solution of ammonium carbonate.

[0171] [6] The manufacturing method according to any one of [1] to [4], wherein the precipitating liquid is water.

[0172] [7] The manufacturing method according to any one of [1] to [6], wherein the reaction solution obtained by adding the above-mentioned raw material solution to the above-mentioned precipitation solution has a pH of 10.0 or less at 25°C.

[0173] [8] The manufacturing method according to any one of [1] to [7], wherein the raw material liquid comprises a liquid generated by recycling waste from lithium-ion secondary batteries.

[0174] [9] A method for manufacturing a positive electrode active material, comprising the following steps:

[0175] The precursor is obtained by the method for manufacturing the precursor of the positive electrode active material as described in any one of items [1] to [8];

[0176] The obtained precursor was mixed with a lithium compound to obtain a mixture; and

[0177] The resulting mixture was calcined.

Claims

1. A method for manufacturing a precursor of a positive electrode active material, comprising the following steps: adding a raw material solution containing Ni, Co, Mn, ammonia, ammonium ions and carbonate ions to a precipitation solution, thereby precipitating carbonates containing Ni, Co and Mn. The concentration of ammonia in the precipitate is lower than the concentration of ammonia in the raw material solution.

2. The manufacturing method according to claim 1, wherein, The raw material solution has a pH of 10.0 to 12.0 at 25°C, and the precipitate solution has a pH of less than 10.0 at 25°C.

3. The manufacturing method according to claim 2, wherein, The precipitate solution has a pH below 9.5 at 25°C.

4. The manufacturing method according to claim 2, wherein, The precipitate solution has a pH below 8.0 at 25°C.

5. The manufacturing method according to claim 1, wherein, The precipitating solution is water or an aqueous solution of ammonium carbonate.

6. The manufacturing method according to claim 1, wherein, The precipitate is water.

7. The manufacturing method according to claim 1, wherein, The reaction solution obtained by adding the raw material solution to the precipitation solution has a pH of less than 10.0 at 25°C.

8. The manufacturing method according to claim 1, wherein, The feed liquid comprises a liquid generated through the recycling of waste from lithium-ion secondary batteries.

9. A method for manufacturing a positive electrode active material, comprising the following steps: The precursor is obtained by the method for manufacturing the precursor of the positive electrode active material as described in claim 1; The obtained precursor is mixed with a lithium compound to obtain a mixture; and The resulting mixture is calcined.

Citation Information

Patent Citations

  • Learned model, control device of injection machine, and method for generating teacher data

    JP2025064483A

  • Positive electrode active material precursor for non aqueous electrolyte secondary cell, positive electrode active material for non aqueous electrolyte secondary cell, method for manufacturing positive electrode active material precursor for non aqueous electrolyte secondary cell, and method for manufacturing positive electrode active material for non aqueous electrolyte secondary cell

    WO2017119457A1